Pedagogika emancypacyjna a pedagogika specjalna – kluczowe kategorie w emancypacyjnym dyskursie niepełnosprawności - Podgórska-Jachnik, Dorota (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
Interest of special education in the issue of emancipation emerges from an opres- sion, often experienced by people with disabilities. Emancipation is usually under- stood as liberation from all kinds of dependence, oppression or fear, as the attain- ment of self-reliance and independence. This justifies the importance of stimulating the activity of emancipation by special educators. The issue, however, is a way of shaping emancipation competences. Although the emancipatory paradigm has not yet been fully utilized within this sub-discipline, it seems to be an inspiring research perspective. The article presents the key issues, discourses and concepts associated with the paradigm of emancipation in special education.